As Ciências Espaciais, o saber e o fazer docente no ensino fundamental - Lima, Miguel Salustiano de (2008)
This study aims to include topics related to Space Science in elementary education from an experiment that aims to rescue the science teachers in public schools of São Tomé, RN, a taste for experimentation and exploration of advanced technologies. During this research with teachers found that they knew enough about the subject, but this knowledge was restricted to the events disclosed by the media. Regarding scientific knowledge, that same surface, they had many conceptual difficulties which hindered the approach of these topics in their classes. To overcome this difficulty, a workshop was held where teachers had the opportunity to discuss the historical aspect of Space Science, some physical concepts related to it, and the conduct of experiments with PET bottle rockets that recover from the curiosity typical of how the science. The results were outlined in the form of Planning Didactic built by teachers and using themes related to space science, from there, discussing content already provided in the composition of the schools curriculum. Therefore, this work allowed the teachers a minimum training required for them to not only reproduce, but readjusted and build, from this, their own paths in the classroom at the fundamental level